Surveys of belugas and narwhals in the Canadian High Arctic in 1996 - Innes, Stuart; Heide-Jørgensen, MP; Laake, Jeff L; Laidre, Kristin L; Cleator, Holly J; Richard, Pierre; Stewart, Robert EA (NAMMCO Scientific Publications, 2002)
The summer range of belugas (Delphinapterus leucas) and narwhals (Monodon monoceros) in Prince Regent Inlet, Barrow Strait and Peel Sound in the Canadian High Arctic was surveyed from 31 July to 3 August 1996 with a visual aerial survey of offshore areas and photographic aerial surveys of concentration areas. The visual survey estimate based on the number of belugas visible to the observers using systematic line transect methods was 10,347 (cv = 0.28). This included corrections for whales that were missed by the observers, observations without distance measurements and an estimate of 1,949 (cv=0.22) belugas from a photographic survey in southern Peel Sound. Using data from belugas tagged with satellite-linked time-depth recorders, the estimate was adjusted for individuals that were diving during the survey which resulted in an estimate of 18,930 belugas (cv = 0.28). Finally, counts of belugas in estuaries, corrected for estuarine surface time, were added to provide a complete estimate of 21,213 belugas (95% CI 10,985 to 32,619). The estimated number of narwhals corrected for sightings that were missed by observers was 16,364 (cv = 0.24). Adjusting this for sightings without distance information and correcting for whales that were submerged produced an estimate of 45,358 narwhals (95% CI 23,397 to 87,932).